ANALYSIS OF DATA ON PROCUREMENT AND USE OF INSULIN IN DIABETES MELLITUS PATIENTS AT THE GENERAL HOSPITAL Dr. FL TOBING SIBOLGA - Hasni, Hasni Yaturramadhan Harahap; Sofyan Syarifuddin; Debi Meilani; Deliwarni Rajagukguk; Fatimah Sari Simatupang; Reni Aprinawaty Sirait (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Abstract Drug management is a series of drug control starting from the process of selection, procurement, distribution, to use. Drug management is closely related to the budget and expenditure of health installations such as hospitals, health centers, and pharmacies. The aim of this study is to determine the suitability of insulin procurement in public hospitals. Dr. FL. Tobing Sibolga with the needs of diabetes mellitus patients in 2022. This research method includes descriptive research, namely by looking at usage reports and insulin request sheets at RSU Dr. FL. Tobing Sibolga. The results of the study showed that insulin was procured at the FL Hospital. Tobing is in accordance with the need/use of insulin throughout 2022 because the amount of procurement is greater than the need. And there is no significant difference in the planned amount of insulin and insulin needs throughout 2022. Keywords: Management, Use, Appropriateness